2018
DOI: 10.1145/3274317
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Friends and Experts on Privacy Decision Making in IoT Scenarios

Abstract: As increasingly many Internet-of-Things (IoT) devices collect personal data, users face more privacy decisions. Personal privacy assistants can provide social cues and help users make informed decisions by presenting information about how others have decided in similar cases. To better understand which social cues are relevant and whose recommendations users are more likely to follow, we presented 1000 online participants with nine IoT data-collection scenarios. Some participants were told the percentage of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…Users wanted to see both expert opinions (authoritative) as well as real users' opinions (crowd-sourced). Social cues and expert recommendations can have a significant impact on users' decisions [11]. Furthermore, users have varied preferences and acceptance of different sources [33] and these sources have inherent biases.…”
Section: Designing the Information Analysis Functionmentioning
confidence: 99%
“…Users wanted to see both expert opinions (authoritative) as well as real users' opinions (crowd-sourced). Social cues and expert recommendations can have a significant impact on users' decisions [11]. Furthermore, users have varied preferences and acceptance of different sources [33] and these sources have inherent biases.…”
Section: Designing the Information Analysis Functionmentioning
confidence: 99%
“…13: Total time for three situations of no-privacy privacy-no update & privacy-data update (Edge-managed\Privacy). decisions about their privacy decisions in an IoT environment (Emami Naeini et al, 2018). Despite the great benefits these studies provide, a missing piece of the puzzle is to observe the user behavior in a real IoT environment, as these studies depend largely on user questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, studies have shown that the privacy preferences can be predicted by observing the user behavior towards privacy using limited number of scenarios (Naeini et al, 2017). Also, social cues can be given to users to allow them to make informed decisions about their privacy decisions in an IoT environment (Emami Naeini et al, 2018). Despite the great benefits these studies provide, a missing piece of the puzzle is to observe the user behavior in a real IoT environment, as these studies depend largely on user questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers from the area of scenario-based survey have introduced many different approaches to create hypothetical scenarios using text, graphics, games, app interfaces, etc. [15,24,43,45]. Among all of these, text-based scenarios are preferred in case of surveying the participants.…”
Section: Representing Contexts With Scenariosmentioning
confidence: 99%